Nosology of Primary Progressive Aphasia and the Neuropathology of Language - Mesulam, M.-Marsel (Adv Exp Med Biol, 2021)
Primary progressive aphasia (PPA) is a neurodegenerative dementia syndrome that can be associated with multiple neuropathologic entities, including Alzheimer’s disease (AD) and all major forms of frontotemporal lobar degeneration (FTLD). It is classified into several subtypes, each defined by the nature of the language domain that is most impaired. The asymmetric neurodegeneration of the language dominant (usually left) hemisphere is the one consistent feature of all PPA variants. This feature offers unique opportunities for exploring mechanisms of selective vulnerability in neurodegenerative diseases. The focal cortical degeneration in PPA has also led to new insights on the neuroanatomy of language. This chapter reviews some of the current trends in PPA research as well as the challenges that remain to be addressed on the nosology, clinicopathologic correlations, and therapy of this syndrome.